Study of Hermeneutics Story 23rd Sanggar Lentera: Literary Research - Ahmad Yasid; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2023)
Poetry is an expression of words with feelings conveyed by the poet, the meaning of each of these words will be found after dealing directly with the reader. So that in this case it is necessary to have a study to reveal the true meaning of each word contained in the poem, which is called the study of hermeneutics. The purpose of this research is to reveal the meaning contained in the Story 23rd poetry anthology by Sanggar Lentera dan Kawan-kawan. The approach used to study this research was hermeneutical studies, the source of the data in this study was Story 23rd anthology of joint poetry by Sanggar lentera and friends, of the many poems collected in the anthology, the researchers took 4 poems to be used as study material in the study. This. The results of this study indicate that from the poems entitled "Pagi Selamat Tidur" and "Rasa dalam Botol", the two poems contain the intention of having a different life that must be lived by the community due to the presence of the covid-19 virus, things that are not usually done it is imperative for them to do it for their own safety. As for the poems entitled "Negeri Kantong Ajaib" and "Politik Korona", the two poems imply that the policies implemented by the government in this country are bad, to the point where the country's economy is damaged due to the Covid-19 virus. Both of these poems contain the intention that there is a different life that must be lived by the community as a result of the Covid-19 virus, things that are not usually done are a must for them to do for their own safety. As for the poems entitled "Negeri Kantong Ajaib and Politik Korona", the two poems imply that the policies implemented by the government in this country are bad, to the point where the country's economy is damaged due to the Covid-19 virus. Both of these poems contain the intention that there is a different life that must be lived by the community as a result of the Covid-19 virus, things that are not usually done are a must for them to do for their own safety. As for the poems entitled "Negeri Kantong Ajaib" and "Politik Korona", the two poems imply that the policies implemented by the government in this country are bad, to the point where the country's economy is damaged due to the Covid-19 virus